Association of gut microbiota and SCFAs with finishing weight of Diannan small ear pigs - Lan, Qun; Lian, Yuju; Peng, Peiya; Yang, Long; Zhao, Heng; Huang, Peng; Ma, Haiming; Wei, Hongjiang; Yin, Yulong; Liu, Mei (Frontiers in Microbiology, 2023)
Finishing weight is a key economic trait in the domestic pig industry. Evidence has linked the gut microbiota and SCFAs to health and production performance in pigs. Nevertheless, for Diannan small ear (DSE) pigs, a specific pig breeds in China, the potential effect of gut microbiota and SCFAs on its finishing weight remains unclear. Here, based on the data of 16S ribosomal RNA gene and metagenomic sequencing, we respectively identified 11 OTUs and 19 microbial species associated with finishing weight. Among these, carbohydrate-decomposing bacteria of the family Streptococcaceae, Lactobacillaceae, and Prevotellaceae were positively related to finishing weight, whereas the microbial taxa associated with intestinal inflammation and damage exhibited opposite effects. Besides, interactions of these microbial species were firstly found to be linked with finishing weight. Gut microbial functional annotation analysis revealed that CAZymes, such as glucosidase and glucanase could significantly affect finishing weight, given their roles in increasing nutrient absorption efficiency. KOs and KEGG pathways analysis indicated that glycolysis/gluconeogenesis, phosphotransferase system (PTS), secondary bile acid biosynthesis, ABC transporters, sulfur metabolism, and one carbon pool by folate could act as key factors in regulating finishing weight. Additionally, SCFAs levels, especially butyrate and acetate level, had critical impacts on finishing weight. Finishing weight-associated species Prevotella sp. RS2, Ruminococcus sp. AF31-14BH, and Lactobacillus pontis showed positive associations with butyrate, and Paraprevotella xylaniphila and Bacteroides sp. OF04-15BH were positively related to acetate. Taken together, our findings provide essential knowledge for manipulating gut microbiome to improve finishing weight. The underlying mechanisms about how gut microbiome and SCFAs modulate pigs’ finishing weight required further elucidation.